The Auditing Process in Intensive Care Unit: A Systematic Review - , Lorena Pereira Bernardo; , Gabriel Pereira Bernardo; , Romulo Figueiredo de Araujo; , Woneska Rodrigues Pinheiro; , Hermes Melo Teixeira Batista (Archives of Current Research International, 2018)
Introduction: The audit process consists of analyzing and verifying errors in a systematic way so that they can be prevented in the future. Objectives: The objective of the present study was to perform a systematic review of articles that involve the audit process in an intensive care unit. Methods: A systematic review of the literature in the PubMed database in search of articles published from January 1, 2002, to August 31, 2016. The research was carried out with the descriptors "medical audit" and "intensive care unit". Results: The audit showed that it is possible to compare the rates of different units, even if they often present large variations in the data. Conclusion: The study showed evidence of the need to perform audits in an intensive care unit, thus optimizing the results and improvements for the patients and the work team.